Highly polar stacking interactions wrap inorganics in organics: lone-pair–π-hole interactions between the PdO4 core and electron-deficient arenes. Issue 23 (26th October 2021) - Torubaev, Yury V.; Skabitsky, Ivan V.; Rozhkov, Anton V.; Galmés, Bartomeu; Frontera, Antonio; Kukushkin, Vadim Yu.
Abstract : Each PdO4 plane of Pd3 (OAc)6 behaved as a 5-center nucleophile (O lone pairs and the d z 2 -Pd II orbital) that interacts with π-donating arenes to afford highly polar circular stacking, where organics wrapped inorganics. Abstract : Cocrystallization of the palladium acetate cluster Pd3 (OAc)6 (abbreviated as [Pd 3 ]) with electron-deficient iodine(i )-based perfluoroarenes (Ar F I: iodopentafluorobenzene, 4-iodoheptafluorotoluene, 1, 4-diiodotetrafluorobenzene, 1, 2-diiodotetrafluorobenzene, and octafluoro-4, 4′-diiodo-1, 1-biphenyl) and iodine-free octafluoronaphthalene gave a series of six cocrystals [Pd 3 ]·(arene) studied by single-crystal X-ray diffractometry. Significant intermolecular noncovalent interactions were verified by a density functional theory study, molecular electrostatic potential and Hirshfeld surface analyses, a combined QTAIM/NCPlot approach, and NBO and energy framework calculations. In five out of six structures, the aromatic rings coupled with cluster [Pd 3 ] via lone pair–π-(Ar F )-hole interactions. The iodine-containing arenes, Ar F I, were additionally involved in halogen bonding with carboxylate O centers, but inorganic–organic stacking still remained the structure-determining interaction. In the stacking, the electron-rich PdO4 plane behaved as a five-center nucleophile providing oxygen lone pairs in addition to the d z 2 -Pd II orbital; this plane complemented the π-acidic surface of the arenes, affording highly polar circular stacking, where organics wrapped inorganics.